Between Politics and Equations: Teaching Critical Mathematics in a Remedial Secondary Classroom. (October 2013) - Brantlinger, Andrew
Proponents of critical mathematics (CM) argue that it has the potential to be more equitable and socially empowering than other approaches to mathematics education. In this article, the author presents results from a practitioner research study of his own teaching of CM to low-income students of color in a U.S. context. The results pertain to the evolution of his reflections about the potentially enhancing relationship between the critical and the mathematical components of CM and the nature of student empowerment as he designed and taught with CM materials. The results point to curricular and instructional factors that present serious barriers to effective implementation of CM at the secondary level.